A biomechanical investigation of three fixation methods for unilateral denis type II sacral fractures using finite element analysis - Zhao, Peishuai; Li, Renjie; Chen, Jiaqiang; Wang, Yongsheng; Guan, Jianzhong; Wu, Min (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveDue to its inherent high instability, the selection of fixation strategies for unilateral Denis type II sacral fractures remains a controversial challenge in the field of traumatic orthopedics. This study focuses on unilateral Denis type II sacral fractures. By applying three different fixation methods, it aims to explore their biomechanical properties and provide a theoretical basis for optimizing clinical fixation protocols.MethodsA ligament-intact three-dimensional finite-element model of a right-sided Denis type II sacral fracture, including ipsilateral superior and inferior pubic rami fractures, was generated. Three fixation models were simulated: (1) S1/S2 transiliac-transsacral screw fixation (S1/S2-TTS); (2) unilateral L4/5 triangular osteosynthesis (UTOS); and (3) bilateral S2-alar-iliac screws combined with an iliosacral screw (BS2AI-ISS). Appropriate material properties, boundary conditions, and loading protocols were assigned. A 500 N axial compressive load superimposed with a 7.5 Nm torque was applied to simulate standing position and multiplanar spinal motion. Biomechanical parameters evaluated included vertical sacral stiffness, maximum von Mises stress within implants, and relative interfragmentary displacement (RID) at the fracture site.ResultsSacrum vertical stiffness: All constructs significantly increased sacrum vertical stiffness compared with the intact model. Normalised stiffness values were 443.18% (S1/S2-TTS), 228.38% (UTOS) and 397.26% (BS2AI-ISS). Maximum implant von Mises stress: Under every loading mode, S1/S2-TTS exhibited the lowest and most evenly distributed stress (range 30.30–49.23 MPa). Maximum stresses ranked from lowest to highest: S1/S2-TTS < BS2AI-ISS < UTOS. Relative interfragmentary displacement: In standing position, mean RID were 0.0313 ± 0.0148 mm (S1/S2-TTS), 0.0736 ± 0.0314 mm (UTOS) and 0.0539 ± 0.0163 mm (BS2AI-ISS). Only the difference between S1/S2-TTS and UTOS reached statistical significance (p = 0.047). Similar patterns were observed in extension, left flexion and left rotation; no significant differences were found in right flexion or right rotation.ConclusionThe present study demonstrates that BS2AI-ISS provides biomechanical stability comparable to both S1/S2-TTS and UTOS for unilateral Denis type II sacral fractures. Notably, BS2AI-ISS achieves this stability without compromising lumbar motion and irrespective of sacral morphologic variations. These findings suggest that BS2AI-ISS may serve as an effective alternative for managing unilateral Denis type II sacral fractures.